Living the work promoting social justice and equity work in schools around the world - Boske, Christa; Osanloo, Azadeh F. (Advances in educational administration ;, 2015)
This unique volume has been written collaboratively by children, families, teachers, school leaders, scholars, and community organization representatives. With each author having a platform to express his or her individual voice, chapters center on the authors' lived experiences (ranging in skills, knowledge, and activism) in promoting social justice and equity in schools. With a focus on long-standing trends in schools regarding ability (both mental and physical), race, ethnicity, class, religion/beliefs/faith, native language, immigration status, gender, sexuality, family structure, and geographical location, the authors demonstrate how they live their work by facilitating courageous dialogue, promoting inclusive practices, and building authentic relationships with those in power as well as those from marginalized populations. Authors reflect on their personal and professional lives and help the reader understand the call that lies within each of them: to live what is just and right for all children.